2021
DOI: 10.1021/acsapm.0c00955
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Melaminium Adipate Lamellae for Adsorptive Removal of Anionic Dyes from Wastewater

Abstract: The growth in industrialization worldwide has resulted in continual discharge of organic dyes that contaminate the aquatic ecosystem. Common adsorbents employed for dye removal are often expensive and non-biodegradable, causing a problem of secondary waste generation on their disposal. Thus, the design of biocompatible, economical adsorbents is of utmost importance. Bis­(melaminium)­adipate adipic acid solvate (BMA), an ionic organic material, was synthesized from commercially available melamine and adipic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
(78 reference statements)
0
11
0
Order By: Relevance
“…Melamine‐based composites with poly(vinyl alcohol) and nickel(II) oxide were tested for the adsorption of an anionic azo dye, Congo red 40,41 . Melaminium adipate was proposed for adsorptive removal of Congo red, from wastewater 42 . These examples illustrate that dye adsorption on melamine sponge alone has to be kept in mind when analyzing the dye adsorption results.…”
Section: Resultsmentioning
confidence: 99%
“…Melamine‐based composites with poly(vinyl alcohol) and nickel(II) oxide were tested for the adsorption of an anionic azo dye, Congo red 40,41 . Melaminium adipate was proposed for adsorptive removal of Congo red, from wastewater 42 . These examples illustrate that dye adsorption on melamine sponge alone has to be kept in mind when analyzing the dye adsorption results.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that certain materials that carry intrinsic positive charges or materials that can be protonated under acidic conditions can remove anionic dyes only and not neutral and cationic dyes based on electrostatic interactions. 38 However, due to a similar chemical nature, different acid dyes can occur in a mixture. Selective removal of certain dyes from a mixture can aid in dye purification and greatly facilitate dye reuse.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Thus, it is crucial to evaluate the effects of salts/high ionic strength on the dye removal process. Furthermore, salts in the dye solution have been found to affect dye adsorption. ,, As reported in the literature, we also used sodium chloride as a model salt to increase the ionic strength of the solution to assess the effect of high salt concentration on dye uptake by the PCD polymer. An increasing concentration of salt (NaCl) solution was added to the dye–polymer solution under acidic conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Therefore, eco-friendly, byproduct-free, and costeffective disinfection techniques are imperative for water treatment. Besides, among the diverse dye removal methods such as adsorption, 12 membrane filtration, 13 photocatalytic degradation, 14 and biological treatment, 15 adsorption is an appealing approach due to its high efficiency, low cost, and portability. 16 Nevertheless, simultaneous disinfection of microbes and dye removal usually require multistep treatments, longer durations, and higher operational cost.…”
Section: ■ Introductionmentioning
confidence: 99%